Application of the Guided Discovery Learning Model to Improve Student Learning Outcomes in Fractions Division Material - Akina Akina; Mufidah Mufidah; Nurul Kami Sani; Gusti Ayu Made Nova Astuti (IKIP Mataram, 2023)
This study aims to obtain a description of the application of the guided discovery learning model to improve student learning outcomes in the matter of dividing fractions in the VA class of SDN 5 Palu. This type of research is Classroom Action Research (PTK) which refers to the research design of Kemmis and Mc. Taggart, namely (1) planning, (2) implementing actions, (3) observation, and (4) reflection. The subjects in this study were all students of VA class at SDN 5 Palu for the 2022/2023 school year with a total of 24 students consisting of 14 female students and 10 male students. The type of data in this study is qualitative data supplemented by quantitative data. Qualitative data collection techniques in this study were observation, interviews, and field notes. The quantitative data collection technique in this study was a written test. This research was conducted in two cycles. The results of the study show that learning with the guided discovery learning model could increase students’ learning outcomes of VA Class of SDN 5 Palu on the matter of division of fractions. This is evidenced by the increase in student learning outcomes from cycle I to cycle II. The learning outcomes of the first cycle were obtained at 62.5%, and the second cycle was obtained at 83.33%. The results of the analysis of the observation sheet of teacher and student activities in cycle 1 were in the sufficient category. In cycle 2, the teacher and student activity observation sheet increased because the teacher activity observation sheet was in the very good category and the student activity observation sheet was in the good category, so that the success indicators of the action have been achieved.